EPIDEMIOLOGY AND EARLY DIAGNOSIS OF CONGENITAL MALFORMATIONS OF SPINAL COLUMN AND SPINAL CORD - G.M. Elikbaev; V.A. Khachatryan; I.B. Osipov; S.A. Sarychev ("Paediatrician" Publishers LLC, 2008)
Etiological factors of congenital malformations of spinal column and spinal cord were described on the basis of literature analysis and results of proper observations. Measures of early diagnosis and prophylaxis of abnormalities, which can decrease rate of children's disablement and mortality, were indicated.Key words: congenital malformation, myelodysplasia, risk factors, early diagnosis, prophylaxis of malformations.